2017
DOI: 10.1186/s13561-017-0181-3
|View full text |Cite
|
Sign up to set email alerts
|

Palivizumab in the prevention of severe respiratory syncytial virus infection in children with congenital heart disease; a novel cost-utility modeling study reflecting evidence-based clinical pathways in Spain

Abstract: Background: Respiratory syncytial virus (RSV) infection remains one of the major reasons of re-hospitalization among children with congenital heart disease (CHD). This study estimated the cost-effectiveness of palivizumab prophylaxis versus placebo, in Spain, from the societal perspective, using a novel cost-effectiveness model reflecting evidence-based clinical pathways. Methods: A decision-analytic model, combining a decision tree structure in the first year and a Markov structure in later years, was constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…[26,[31][32][33][34][35][36][37][38][39][40] Unfortunately, only a few studies were focused on this group of patients alone in areas with a distinct RSV season, and none of which were population-based. [26,31,33,40,41] These studies were mainly based on either hypothetical patient cohorts or decision-analysis models using ICER/Quality Adjusted Life year (QALY) to assess cost-effectiveness with an exceedingly wide range reported from €9,259 to US$114,337/QALY. [33,40,41] Despite a very favorable ICER/QALY was reported by Nuijten et al, a scenario analysis excluding mortality from the model was reported to raise the ICER/QALY signi cantly from €9,259 to €123,439/QALY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26,[31][32][33][34][35][36][37][38][39][40] Unfortunately, only a few studies were focused on this group of patients alone in areas with a distinct RSV season, and none of which were population-based. [26,31,33,40,41] These studies were mainly based on either hypothetical patient cohorts or decision-analysis models using ICER/Quality Adjusted Life year (QALY) to assess cost-effectiveness with an exceedingly wide range reported from €9,259 to US$114,337/QALY. [33,40,41] Despite a very favorable ICER/QALY was reported by Nuijten et al, a scenario analysis excluding mortality from the model was reported to raise the ICER/QALY signi cantly from €9,259 to €123,439/QALY.…”
Section: Discussionmentioning
confidence: 99%
“…[26,31,33,40,41] These studies were mainly based on either hypothetical patient cohorts or decision-analysis models using ICER/Quality Adjusted Life year (QALY) to assess cost-effectiveness with an exceedingly wide range reported from €9,259 to US$114,337/QALY. [33,40,41] Despite a very favorable ICER/QALY was reported by Nuijten et al, a scenario analysis excluding mortality from the model was reported to raise the ICER/QALY signi cantly from €9,259 to €123,439/QALY. [41] Judging from the fact that the RSV related mortality in this group of patients reported from the REGAL series covers a wide range from 0 to 3.3%, we think using ICER/QALY in hypothetical model may result in signi cant inaccuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these related to various iterations of the JCVI (West Midlands HTA) model carried out by Wang et al [24][25][26] A further study was an evolution of this approach, funded by AbbVie and published in 2013. 27 We also identified five other studies: one from the UK, 4 two from Spain, 28,29 one from the Netherlands 30 and one from Canada. 31 These publications used approaches that were either at odds at those adopted by JCVI or simply reinforced the conclusions of the two key models, therefore, we did not consider these models further and focused on the West Midlands HTA model carried out by Wang et al [24][25][26] and the updated Bentley et al 27 model.…”
Section: Targeted Literature Reviewmentioning
confidence: 99%
“…The model demonstrated that palivizumab prophylaxis results in more quality-adjusted life years (QALY) than placebo in children with CHD. Palivizumab prophylaxis was shown to be a cost-effective health-care intervention according to the commonly accepted standards of cost-effectiveness in Spain [35].…”
Section: Pharmacoeconomicsmentioning
confidence: 99%